Characterisation of beta-globin gene mutations in malaysian children: a strategy for the control of beta-thalassaemia in a developing country - Thong, M.K.; Tan, J.; Tan, K.L.; Yap, S.F. (2005)
beta-thalassaemia major, an autosomal recessive hemoglobinopathy, is one of the most common single gene disorders in multi-racial Malaysia. The control of beta-thalassaemia major requires a multi-disciplinary approach that includes population screening, genetic counselling, prenatal diagnosis and the option of termination of affected pregnancies. To achieve this objective, the molecular characterisation of the spectrum of beta-globin gene mutations in each of the affected ethnic groups is required. We studied 88 consecutive unrelated individuals and their respective families with beta-thalassaemia (74 beta-thalassaemia major, 12 HbE-beta-thalassaemia, 2 with HbE homozygotes) and four individuals with beta-thalassaemia trait that contributed a total 180 alleles for study. Using a 2-step molecular diagnostic strategy consisting of amplification refractory mutation system (ARMS) to identify the 8 most common mutations followed by other DNA-based diagnostic techniques, a total of 177 (98.3 per cent) of the 180 beta-thalassaemia alleles were characterised. One out of 91 (1 per cent) of the Chinese alleles, one out of 46 (2.2 per cent) Malay alleles and one out of two Indian alleles remained unknown. A 100 per cent success rate was achieved in studying the Kadazandusun community in this study. A strategy to identify beta-globin gene mutations in Malaysians with beta-thalassaemia is proposed based on this outcome.